2000
DOI: 10.1359/jbmr.2000.15.9.1825
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression with FK506 Increases Bone Induction in Demineralized Isogeneic and Xenogeneic Bone Matrix in the Rat

Abstract: The aim of the present study was to investigate a systemic induction of bone formation in rats by immunosuppression with FK506 (1 mg/kg body weight intraperitoneally [ip]) in a model of osteoinduction of isogeneic and xenogeneic demineralized bone matrix (DBM) for a period of 28 days. In particular, alterations of in vitro cytokine synthesis and changes of lymphocyte subsets were studied. DBM was implanted intramuscularly in the abdominal wall of Lewis rats (seven per group). Blood was sampled on days ؊7, 0, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…5,6 This is because immunosuppressants influ- ence on bone metabolism indirectly by reducing the amounts of cytokine produced by cells of the immune system. 7 However, recently there have been some studies regarding the effects of immunosuppressants on early bone formation and repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 This is because immunosuppressants influ- ence on bone metabolism indirectly by reducing the amounts of cytokine produced by cells of the immune system. 7 However, recently there have been some studies regarding the effects of immunosuppressants on early bone formation and repair.…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that this was due to the immunosuppressing role of FK506, because immune reactions can inhibit bone induction from heterotopically transplanted DBM. 7 Yoshikawa et al found that FK506 promoted the formation of bone in MSCs/hydroxyapatite composites in a model of allografts, when it was administered as an immunosuppressant. 8 Isomoto et al investigated the effect of three immunosuppressants on the osteogenic differentiation of MSCs and found that rapamycin decreased the osteogenic effects of Dex; FK506 increased APase activity and the calcium content of the cells; and CsA had a negligible effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that white blood cells are responsible for inflammatory reaction in the early stage of fracture healing. The exact influence of higher white blood cell concentration on the β-TCP in the cage in our study is unclear, but in the literature, suppression of leukocyte proliferation or function resulted in higher bone formation and mechanical bending moment in rats [9,28].…”
Section: Discussionmentioning
confidence: 88%
“…Some researchers have reported that FK506 promotes osteoblast activity and is a useful agent for induction of bone formation or for allogeneic bone grafting. 29,30 To determine whether our results were depended on the immunosuppressant or osteogenic effect of FK506, we examined the expression of BMP-2 and ALP mRNA at 1, 3, 5, 7, and 9 days after injection into nude rats and we also performed radiographic, histologic, histomorphometric, and biological assessment of nude rats at 21 days after injection. In the FK506 group, BMP-2 expression remained high until 5 days after administration, but was decreased markedly from 7 days onwards.…”
Section: Discussionmentioning
confidence: 99%